PERLINDUNGAN HUKUM TERHADAP ANAK YANG LAHIR DI LEMBAGA PEMASYARAKATAN BERDASARKAN HUKUM POSITIF INDONESIA - I GUSTI AGUS YUDA TRISNA PRAMANA; I WAYAN JEKALAYA MADE SUARTINI; I DEWA NYOMAN GDE NURCANA (GANEC SWARA, 2024)
Basically, law enforcement will always lead to 3 (three) important things, namely the fulfillment of legal certainty, the fulfillment of justice, and the fulfillment of benefits. When these 3 (three) fulfillments are fulfilled, it can be said that law enforcement has succeeded in achieving its objectives. The value of justice in the foundation of the Indonesian state is also contained in the fifth principle of Pancasila. Human life includes physical and spiritual life, so justice also includes justice in fulfilling the essential demands for physical and spiritual life for all Indonesian people equally, especially for children, including children born in correctional institutions, so this research specifically discusses regarding the protection of children born in correctional institutions. The type of research used in this writing is included in the category/type of normative legal research. Normative legal research methods are methods or methods used in legal research which are carried out by examining existing legal sources. So in this research there are several forms of legal protection for children's rights regulated in Indonesian Positive Law. Regulations regarding legal protection of children's rights can be found in the Constitution of the Republic of Indonesia of 1945, and Law of the Republic of Indonesia no. 39 of 1999 concerning Human Rights. If you look at the regulations regarding the rights of children born in prison, then in fact there are many children's rights that are violated by PP No. 32/1999. Furthermore, regulations regarding the protection or guarantee of the rights of children born in prisons in accordance with Article 20 paragraphs (3), (4), and (5) PP 32/1999 are not in accordance with or conflict with the provisions regulated in Article 28B paragraph (2) 1945 Constitution, Article 5 letter g of the Corrections Law and Article 59 paragraph (1) of the Human Rights Law